Phase Separation Regulates Metabolism, Mitochondria, and Diseases - Chuan Gao; Peng Ding; Changqing Zhang; Junjie Gao (MedComm)
ABSTRACT As a physicochemical mechanism, phase separation is a spatial and temporal regulator of specific molecules within a cell, and it provides a new perspective for understanding cellular pathophysiology. Phase separation is closely associated with multiple metabolic processes in the body, including the regulation of key metabolic enzymes and the physiology of mitochondria. Mitochondria also regulate multiple physiological functions through phase separation, including protecting healthy mitochondria and mRNAs in oocytes and regulating crosstalk between nuclear and mitochondrial. Importantly, abnormal phase separation in vivo is associated with the development of diseases, including cancer, neurodegenerative diseases, endocrine disorders, skeletal system diseases, and infectious diseases. This review summarizes the relationship between phase separation and metabolism under both physiological and pathological conditions, as well as the therapeutic potential of phase separation in the treatment of relevant diseases, aiming to explore the possibility of treating diseases by regulating phase separation.